(untitled) (Nepalese Journal of Radiology, 2022)
Introduction: Low back pain secondary to degenerative disc disease is a condition that affects young to middle-aged persons with peak incidence at approximately 30-39 years. Magnetic Resonance Imaging (MRI) is the standard modality for detecting disc pathology. This study is being conducted to review the pattern of spinal degenerative diseases in patients referred to our institution. Methods: A retrospective study was conducted at Gandaki Medical College Teaching Hospital & Research Centre (GMCTHRC) from January 2018 to April 2018 with approval from the Institutional Review Committee of Gandaki Medical College Teaching Hospital and Research Centre. The MRI findings were noted i.e. disc desiccation, disc bulge (diffuse, symmetrical and asymmetrical), disc protrusion, neural foramen narrowing, traversing nerve root compression, exiting nerve root compression and posterior annular ligament tear. Results: Out of 98 patients enrolled in the study mean age being 41 years. Disc bulge as most common finding seen in 89 (90.8%) followed by protrusion 50 (51.1%) neural foraminal narrowing (NFN) 72 (73.4%) traversing nerve roots (TNR) compression 58 (59.1%) and exiting nerve root (ENR) compression 22 (22.4%). Conclusions: The study shows that degenerative disc diseases remain the cause of morbidity in the most productive years of life (30-40 years). Large volumes of MRIs performed for this condition represent a significant economic and healthcare burden in a developing country like Nepal.